Korelasi Penambahan Berat Badan Diantara Dua Waktu Dialisis denganKualitas Hidup Pasien Menjalani Hemodialisa - Wahyuni Wahyuni; Winda Irwanti; Sofyan Indrayana (Alma Ata University Press, 2014)
Hemodialysis is a static treatment to substitute kidney function. Without a substitute therapy for kidney, a death as a results of metabolic abnormality can occur rapidly. Common issues on clients undergoing hemodialysis are gaining body weight in between two times dialysis which can affect the quality of life of patients if it is not get the good treatment. This research aimed to identify corelations weight gain in between the two time of dialysis to the quality of life of patients with chronic renal failure who underwent hemodialysis in RSUD Panembahan Senopati Bantul. This was a descriptive correlation study with cross-sectional design, samples were taken with accidental sampling technique consisted of 61 people. Data were analized by Kendal Tau Test(τ). The results of the statistics kendal tau (τ) indicated its value pearson kendal tau (-0,009) with p value 0,938, the ﬁ gures were larger than standard signiﬁcance α: 0.05, thats mean the hypothesis of this research was rejected. Conclusion, there was no a signiﬁ cant corelation weight gaining in between two time of dialysis to the quality of life of patients with chronic renal failure who underwent hemodialysis in RSUD Panembahan Senopati Bantul.